A STUDY OF THE TEXTUAL HISTORY, DOCTRINAL CONTENT AND PHILOSOPHY OF TWELVER SHĪʿĪ LITURGY FROM THE PERIOD OF THE IMĀMS TO ʿABBĀS AL-QUMMĪ (D.1359/1940) - Vinay Khetia (My University, 2022)
This dissertation explores the historical, doctrinal, and philosophical aspects pertaining to Twelver Shīʿī liturgy. In doing so, it brings to light the broad historical contours which established its textual development and proliferation from the period of the Imāms until that of Shaykh ʿAbbās al-Qummī. This historical development entailed the production of the liturgical genre as a textual tradition that developed from the 2nd/8th century. It is believed that portions of this early textual tradition went on to form the basis of later liturgical collections such as al-Kulaynī’s Kitāb al-duʿāʾ, Ibn Qūlawayh’s Kāmil al-ziyārāt and al-Ṭūsī’s Miṣbāḥ al-mutahajjid. This is also indicative of a profound interest in liturgical material by both the scholars who compiled this material and the faithful who performed it, which is evidenced by the repeated copying and transmission of such texts in various parts of the Muslim world. These liturgical texts (duʿāʾ and ziyāra) are also replete with philosophical and theological motifs which underly their function as a means of developing Shīʿī piety and a religious identity that focuses upon complete submission to the Imāms of the People of the House (ahl al-bayt). Considering the above, the texts, when recited and enacted, may be described as a form of performative theology in the Twelver Shīʿī tradition. It is this performative theology which aided in the development and fortification of Twelver Shīʿī identity, especially in light of their minority and often beleaguered social-political position at various times in history. Through an in-depth investigation into the culture and practice of the rigorous and systematic transmission of liturgical texts, this dissertation provides, for the first time, clear evidence of a method for preserving the liturgical compositions that were attributed to the Imāms. With a selection of words and phrases drawn from these texts, a sensitive analysis is made of their theological and cosmological underpinnings. It is hoped that such an analysis will pave the way for further consideration of this, until now, somewhat neglected field of Islamic Studies.
TWELVER SHĪʿĪ LITURGY FROM THE PERIOD OF THE IMĀMS TO ʿABBĀS AL-QUMMĪ
This doctoral thesis is on the subject of Islamic and Shia liturgy or prayer. it covers its history, philosophy and doctrinal content
Keywords: Islamic Studies; Religious Studies; Prayer; Dua; Shia; Islam; Shiism; History; Religion; Liturgy; Ziyarat